La mémoire de projet : véhicule d’intégration de l’ergonomie et de la SST à la conception ? - Fernande Lamonde; Anabelle Viau-Guay; Philippe Beaufort; Jean-Guy Richard (Perspectives Interdisciplinaires sur le Travail et la Santé)
A major issue for ergonomists and preventionists is to have the project process evolve in order to effectively influence the design of work situations. This article discusses a continuous project-improvement mechanism that they could use to advantage to support their efforts : project memory. First, this article summarizes what is being said about this tool in the literature from the fields of project and organization management. It then proposes, to ergonomic and OHS professionals, lessons to be drawn from the project memory to support their design integration efforts : infiltrating the continuous project improvement activities that are taking place in the day-to-day life of the organization ; promoting the implementation of project memory practices, even sporadically, particularly process-oriented memory (to complement the more classical result-oriented memory) and carried out by all the project participants, including themselves.